Buffalo milk production in brazil and colombia: Genotype by environment interaction - Hurtado-Lugo, Naudin; Cerón-Muñoz, Mario; Aspilcueta-Borquis, Raul; Sesana, Roberta; de Albuquerque, Lucia Galvão; Tonhati, Humberto [UNESP] (My University, 2011)
The objective of this study was to determine whether there is a genotype by environment interaction (GxE) for dairy buffaloes in Brazil and Colombia. The (co)variance components were estimated by using a bi-trait repeatability animal model with the REML method. Each trait consisted in the milk yield obtained in both countries. Contemporary group (herd, year and season of parity) and age at parity (linear and quadratic covariate) fixed effects, along with the additive genetic, permanent environment, and the residual random effects were included in the model. Genetic, permanent environmental and residual variance and heritabilities were different for both countries. The genetic correlations for milk yield between Brazil and Colombia were low (between 0.10 and 0.13), indicating a GxE interaction between both countries. Knowing that this interaction influences the genetic progress of buffalo populations in Brazil and Colombia, we recommend choosing sires tested in the country they will be used, along with conducting joint genetic evaluations that consider GxE interaction effects.
Keywords: Genetic correlation; Genetic progress; Genotype by environment interaction; Milk yield; Animalia; Bubalus